Relevansi Nilai Informasi Akuntansi dengan Pendekatan Terintegrasi: Hubungan Nonlinier - Katarina Dyah Kristanti; Luciana Spica Almilia (The Indonesian Journal of Accounting Research, 2013)
The purposes of this research are to know: (1) is there any nonlinearity relationship between earnings and stock return, (2) is there any nonlinearity relationship between cash flow and stock return that is moderated with earnings/price ratio, (3) is there any nonlinearity relationship between accrual and stock return. The result of this research can used as judgment for the practise in decision making with information earnings, cash flow and accrual and what is primary to be expected. This research uses 41 manufacturing firms that listed in Jakarta Stock Exchanges, which are selected by using purposive random sampling. Those selected firms announced their financial statement during 1998 until 2002. Assumption classics test is done, there are normality test with Jarque-Bera (JB) Test of Normality, linierity test with scatterplot, heteroscedasticity test with White Heteroskedasticity test, autocorrelation test with Durbin-Watson test. The hypothesis is tested by NLS (Non Linier Least Square) model regression. Value relevance earnings (unexpected) begin lost their value relevance but to earnings level, there are significant examination year. Value relevance component cash flow are consistent with Hodgson and Clarke (1998) research that give the greater explanatory power. Accrual is significant at two days before publication financial statement.